2014
DOI: 10.1007/s10113-014-0604-1
|View full text |Cite
|
Sign up to set email alerts
|

Land-use and land-cover effects on regional biodiversity distribution in a subtropical dry forest: a hierarchical integrative multi-taxa study

Abstract: Land-use and land-cover effects on regional biodiversity distribution in a subtropical dry forest: a hierarchical integrative multitaxa study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 52 publications
2
63
0
6
Order By: Relevance
“…This result matches that of Torres et al (2014), who found that the response of the probability of presence of all the analyzed amphibian species in Argentinean northwestern Dry Chaco to woody biomass was negative. The importance of open habitats for Leptodactylus species suggests that these species evolved in landscapes which were more similar to open habitats than to forests, a scenario proposed for the pre-European landscape of the Chaco (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1972; Adámoli et al, 1990; Bucher & Huszar, 1999), in which the substantial contemporary woodland advance has been a result of domestic livestock overgrazing (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result matches that of Torres et al (2014), who found that the response of the probability of presence of all the analyzed amphibian species in Argentinean northwestern Dry Chaco to woody biomass was negative. The importance of open habitats for Leptodactylus species suggests that these species evolved in landscapes which were more similar to open habitats than to forests, a scenario proposed for the pre-European landscape of the Chaco (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1972; Adámoli et al, 1990; Bucher & Huszar, 1999), in which the substantial contemporary woodland advance has been a result of domestic livestock overgrazing (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The importance of open habitats for Leptodactylus species suggests that these species evolved in landscapes which were more similar to open habitats than to forests, a scenario proposed for the pre-European landscape of the Chaco (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1972; Adámoli et al, 1990; Bucher & Huszar, 1999), in which the substantial contemporary woodland advance has been a result of domestic livestock overgrazing (Morello & Saravia Toledo, 1959a; Morello & Saravia Toledo, 1959b; Adámoli et al, 1990). Thus, savannas might have been an important cover type where part of the chacoan biota evolved (Torres et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore prioritized information consistency by using only one information source for the whole study area, and we chose a dataset that has been used in others studies in order to facilitate integration with these studies (e.g. Torres et al, 2014).…”
Section: Rainfallmentioning
confidence: 99%
“…Land use/cover change via altering habitat area and spatial distribution of habitat patches affect the structure and spatial heterogeneity of a landscape (Broadbent et al 2012). Landscape changes and habitat fragmentation in protected areas and ecologically sensitive regions can have negative impacts on wildlife populations (Lian et al 2011;Torres et al 2014).…”
Section: Introductionmentioning
confidence: 99%